Pendidikan Berbasis Cinta Prespektif KH.Hasyim Asy’ari dan Syaikh Al-Zarnuji: Studi Komparasi Kitab Adab Al-’Alim Wa Al-Muta’alim dan Ta’lim Al Muta’alim - Jalaludin Jalaludin; Zaimudin Zaimudin; Sapiudin Shidiq (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
In modern reality, the relationship between teachers and students is increasingly losing the depth of the values ​​of love and affection. Education tends to be directed solely at academic achievement without paying attention to the formation of personality. Even teachers are often not appreciated properly and students lose their direction in seeking role models. Amidst the urgency of creating a humane education, two works of classical Islamic scholars, namely Adab al-‘Alim wa al-Muta‘allim by KH. Hasyim Asy‘ari and Ta‘lim al-Muta‘allim by Syaikh Az-Zarnuji, have emerged as important references. These two books not only discuss learning methods or the nature of knowledge, but more deeply, namely Making Love an Ecosystem in Education and Learning. The objectives of the research are (1) How is the Concept of Love-Based Education from the Perspective of KH. Hasyim Asy'ari and Syaikh Al-Zarnuji (2) how love becomes the basis of a love-based education ecosystem in learning and education. The approach in the research is Qualitative with the type of content analysis research on the text of the book Adab Al-'Alim wa Al-Muta'alim in chapters three and seven, the texts of the book Ta'lim Al-Muta'alim related to Love-Based Education. The data collection technique uses documentation, data processing techniques and data analysis using comparison, to analyze more deeply the researcher also uses the theory developed by Miles Hubberman, namely data reduction, data display and verification. As for triangulation, namely Triangulation of Sources and Techniques. The results of the study (1) KH. Hasyim Asy'ari and Syaikh Al-zarnuji have the same view on the importance of compassion in education, but with different emphases, KH. Hasyim Asy'ari emphasizes the structure of adab and spiritual responsibility, while Syaikh Al-zarnuji emphasizes righteous intentions and clean emotional relationships, (2) Integrating compassion as an educational ecosystem, reviving compassion as the main principle of education, building a humane atmosphere.